Circlator: automated circularization of genome assemblies using long sequencing reads. Issue 1 (December 2015) - Hunt, Martin; Silva, Nishadi; Otto, Thomas; Parkhill, Julian; Keane, Jacqueline; Harris, Simon
Abstract The assembly of DNA sequence data is undergoing a renaissance thanks to emerging technologies capable of producing reads tens of kilobases long. Assembling complete bacterial and small eukaryotic genomes is now possible, but the final step of circularizing sequences remains unsolved. Here we present Circlator, the first tool to automate assembly circularization and produce accurate linear representations of circular sequences. Using Pacific Biosciences and Oxford Nanopore data, Circlator correctly circularized 26 of 27 circularizable sequences, comprising 11 chromosomes and 12 plasmids from bacteria, the apicoplast and mitochondrion ofPlasmodium falciparum and a human mitochondrion. Circlator is available athttp://sanger-pathogens.github.io/circlator/ .